Fixed bed column adsorption of Cr(VI) from aqueous solution using nanosorbents derived from magnetite impregnated Phaseolus vulgaris husk - Srivastava S.; Agrawal S.B.; Mondal M.K. (My University, 2025)
Phaseolus vulgaris husk impregnated with magnetite (Fe 3 O 4 ) was successfully synthesized by co-precipitation method as nanosorbents for characterization study and utilized for Cr(VI) biosorption from aqueous solution. Scanning electron microscopy, transmission electron microscopy, Fourier Transform infrared spectroscopy, and BET techniques were applied for nanosorbent characterization. In fixed bed column condition, influence of important process parameters like pH, influent concentration, flow rate, and bed height on adsorption of Cr(VI) by magnetite impregnated P. vulgaris husk were investigated. Maximum adsorption capacity at pH 1.16, influent Cr(VI) concentration 100 mg/L, flow rate 5 mL/min, and bed depth of 3.2 cm was calculated to be 53.28 mg/g. The breakthrough time and column exhaustion time showed inverse relation with pH, influent concentration, flow rate, and direct with bed depth. Bohart–Adams, Thomas, and Yoon–Nelson models were used to predict column performance. Compared to Bohart–Adams, Thomas, and Yoon–Nelson models fitted well to experimental data. © 2018 American Institute of Chemical Engineers Environ Prog, 38: S68–S76, 2019. © 2018 American Institute of Chemical Engineers